Prevention of Domestic Violence through Gender Equality Literacy and Women's Economic Empowerment in Ciamis By the ABCD Approach - Sumadi; Lilis Nurteti; Haqibul Mujib (al-Afkar, Journal For Islamic Studies, 2023)
Domestic violence (KDRT) is a very complex problem. Domestic violence is like an iceberg, which looks small on the surface but is actually rooted and big in shape, sinking downwards. The trend in Indonesia is increasing every year. Data on domestic violence (KDRT) is always the most reported case every year. The number of domestic violence cases that were reported during 2017 was around 300 thousand cases. The dominant victims are wives/women (Komnas Perempuan, 2019). But the impact can be broad to violence against children. In the Regency area, data on divorce in Ciamis Regency shows that most divorces occur due to domestic violence (KDRT). The divorce rate in Ciamis Regency has always been high at the national level. In 2019, the divorce rate in Ciamis was ranked 5th nationally. Of these, 719 divorce cases were caused by domestic violence (PA Ciamis, 2019). According to previous research, the causes of domestic violence have many variables, including: (a) masculine religious understanding; (b) patriarchal culture; (c) low literacy on gender equality; (d) education; and economy. Therefore, efforts to reduce domestic violence are carried out using the ABCD method which includes increasing understanding of religion that is friendly to partnerships, increasing literacy on gender equality, and economic empowerment.